Preparation method of flame-retardant, washable and melt-drop-resistant polyurethane coating
By introducing carbon-forming agents, polyhydroxy single-walled nanotubes and glucose modifications into polyurethane coatings, flame-retardant, water-washable, melt-drip resistant polyurethane coatings are prepared, which solves the problem of poor heat resistance and poor heat resistance of existing coatings in PCB processing. Eliminates adhesion issues and achieves efficient drilling accuracy and board performance.
Patent Information
- Application Number
- CN202411428593.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-12
- Publication Date
- 2025-01-17
- Estimated Expiration
- 2044-10-12
AI Technical Summary
The existing washable paints have problems such as poor heat resistance, easy coatings adhere to PCB holes, and moderate adhesion in PCB processing, which affect the drilling accuracy and the use performance of the circuit board.
By utilizing the prepolymerization reaction of char-forming agent and polyhydroxy single-walled nanotubes, porous carbon layer modifications and glucose modifications to extend the chain, the flame retardancy, water washability and degradability of polyurethane are improved, and flame retardant, Washable, drip-resistant water-based polyurethane coating.
The coating produces no melt droplets when heated, releases low heat, and improves the flame retardancy of polyurethane. It also has good washability and degradability, is suitable for PCB processing, and improves drilling accuracy and circuit board performance.
Smart Images

Figure BDA0005082916390000151 
Figure BDA0005082916390000162 
Figure BDA0005082916390000171
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing a waterborne polyurethane coating, in particular to a method for preparing a flame-retardant, water-washable and drip-resistant waterborne polyurethane coating. Background Art
[0002] Temporary protective coatings are similar to general protective coatings, and can protect and remove dirt on the surface of the protected object. The difference is that the former has a short action time and mainly plays a protective role during processing, transportation or temporary storage. After the processing, transportation and storage process, the coating layer needs to be removed from the surface of the protected object. After the coating is removed, the original functions and properties of the protected object cannot be damaged or negatively affected. This kind of coating that plays a temporary protective role is also called removable coating or washable coating. Washable coatings can form a tightly structured film layer after being applied to the protected object, which can isolate the protected material from the outside world. At the same time, surface adsorption, adhesion and other effects during the film formation process can absorb dirt on the protected object.
[0003] Washable coatings are often removed from the surface of the protected object by soaking or washing with a specific solvent. The film must have a certain solubility in the solvent, which includes water, acid and alkali liquids, or specially formulated paint strippers. It is mainly used for glass and metal surface protection, or for vacuuming walls and floors and purifying the air.
[0004] PCB circuit boards are the cornerstone of electronic components. During the manufacturing process of PCB circuit boards, drilling accuracy is one of the core indicators for measuring PCB quality. With the continuous introduction and high attention of government policies and regulations, removable coatings are the key to promoting the transformation and upgrading of the Chinese coatings industry to practice high-quality development and green and sustainable development, and washable coatings are the key to affecting PCB drilling accuracy. Applying removable coatings on aluminum plates, and then attaching the aluminum plates with removable coatings to circuit boards (copper substrates, copper clad boards), and then drilling can improve the drilling accuracy of circuit boards. Coatings are a consumable material, and the PCB needs to be cleaned after the drilling operation is completed to remove the coating film. The washable paints used in PCB processing on the market today generally have the following pain points: First, PCB drilling requires drilling with aluminum plate coatings, but traditional washable paints have poor heat resistance and cannot withstand the heat released during drilling operations, causing the coating film to partially or completely melt, affecting drilling accuracy; second, paint splashed during drilling is easy to adhere to the epoxy resin through-holes of the PCB, which is difficult to handle, and residual paint is easy to cause moisture, mold, and corrosion of the circuit board, affecting the performance and life of the circuit board; third, the resin adhesion between the PCB and the aluminum plate is not moderate, the adhesion is poor, the metal (aluminum plate) compatibility is poor, and it is difficult to protect. The adhesion is too strong and it is also difficult to be cleaned.
[0005] Jia Danfeng (Jia Danfeng. Preparation of water-washable temporary protective coating [D]. South China University of Technology, 2017) et al. prepared water-soluble acrylic resin by solution free radical polymerization method, using acrylic acid (AA), hydroxyethyl methacrylate (HEMA) and acrylamide (AM) as functional monomers, butyl acrylate and methyl methacrylate as soft and hard monomers, azobisisobutyronitrile (AIBN) as initiator, and dimethylethanolamine as neutralizer. Then the water-soluble acrylic resin was compounded with the emulsion to prepare a water-based compounded resin for resin coating. The water-based compounded resin was compounded with fillers, water-soluble polymers and other additives to prepare a water-washable temporary protective coating. It was found that the adhesion of the film was level 2, and the demolding time at 50°C was 50s, showing a good water washing time. However, this technology did not take into account the defect that the temporary coating film would adhere to the metal material when heated during use, causing the film to melt and be difficult to clean, and did not study core indicators such as PCB drilling accuracy.
[0006] Invention patent CN202210702763.5 involves using polyvinyl alcohol (PVA) resin as the main resin to improve the flexibility of the paint film; using polyether-modified acrylic resin as the modified resin to improve the adhesion of the paint on soft PVC and improve the water solubility of the PVA resin. At the same time, a small amount of acrylic-modified polyurethane (PUA) resin is used as the second modified resin to improve the bonding strength with soft PVC and resist cracking caused by deformation of the material. The invention also adds carboxylic acid-type propyl beet amphoteric surfactants to the coating, which has the dual effects of thickening and improving water washing residues, thereby accelerating the dissolution rate of the paint film when washed with water. Therefore, the coating provided by the invention has excellent flexibility, is not easy to crack, and has a good water washing effect. However, the patent involves cleaning of soft PVC, which is different from the use environment of the coatings used for aluminum plates and PCB epoxy resin boards, and does not involve the standard requirements for flame retardancy of acrylic esters.
[0007] Invention patent CN2015105882116 A kind of anti-carburizing coating that can be washed and removed after quenching is prepared by the following mass percentage components: 25-35% boric acid, 15-25% filler, 15-25% aluminum dihydrogen phosphate, 1-5% coloring pigment and 30-40% water. The invention also discloses a preparation method of the above anti-carburizing coating that can be washed and removed after quenching. The anti-carburizing coating can be removed by washing after carburizing heat treatment, thereby solving the problem that traditional anti-carburizing coating is difficult to peel off after carburizing heat treatment. Inorganic high temperature resistant materials are used as anti-carburizing agents in the formula of anti-carburizing coating. The anti-carburizing coating formed after the anti-carburizing agent is brushed on the surface of the workpiece has good adhesion, and does not peel or flow at high temperature, and does not affect the carburizing atmosphere. The invention does not involve a film-forming agent with polyurethane resin as a film.
[0008] Invention patent 201910576686.1 relates to a glue-coated aluminum-based cover plate for PCB drilling and its preparation method, wherein the water-soluble composite polymer resin layer has moderate toughness and can play a guiding role during the falling process of the drill needle, thereby improving the drilling accuracy; at the same time, the hot-melt resin in the water-soluble composite polymer resin layer can lubricate the drill bit and cool the drill needle during drilling, thereby effectively improving the roughness of the hole wall, reducing wire winding, reducing the drill bit temperature, and extending the service life of the drill needle; in addition, the water-soluble composite polymer resin layer has good water solubility, is easy to handle after drilling, and is not easy to adhere to the holes in the PCB, thereby ensuring the drilling quality. The disadvantage of this resin is that it has not studied whether the glue attached to the PCB hole during drilling can be cleaned, and has not conducted in-depth research on the bonding of the film generated by the drill bit when heated.
[0009] Invention patent 201310504176.6 involves the following steps: (1) pre-processing the circuit board substrate, drilling through holes and copper deposition, board surface electroplating, outer layer circuit pattern transfer, pattern electroplating, etc.; 2) back drilling on PCB board 4 to detect whether the back drilling hole depth is qualified; 3) alkaline etching and photosensitive solder mask are performed on the drilled back drilling hole to finally obtain the finished product. The key points of its technical solution are: when back drilling, the drill belt coefficient used in the drilling through hole process should be modified according to the expansion and contraction data that appears in the process from drilling through holes to drilling back holes on PCB board 4, so as to keep the drill belt data consistent with the actual expansion and contraction; the drilling surface in the drilling through hole process is consistent with the drilling surface during back drilling; a layer of phenolic pad 6 is added on the top of PCB board 4; the depth accuracy and position accuracy of the existing back drilling holes on PCB board 4 can be effectively improved to ensure the integrity of the signal transmission on PCB board 4. The invention does not study the cleaning of the coating film and the bonding of the drill film and the adhesion of fragments.
[0010] In summary, the existing technology does not involve the research on water-based polyurethane coatings for washable aluminum cover plates, nor does it conduct a comprehensive study on the burning droplets of water-washable coatings applied on aluminum cover plates, the heat tolerance (pkHHR, THR), the washability of the film on the aluminum cover plates, the hole position accuracy, hole wall roughness and drill temperature of the PCB core, and the aperture melt and other indicators, nor does it conduct a comprehensive study on the degradation of water-washable coatings. The above indicators are the key to evaluating the performance of water-washable coatings, so research is imperative. Summary of the invention
[0011] The present invention aims to solve the problem of requiring a polyurethane coating with low heat release, resistance to molten droplets, water washability and degradability in PCB processing. Aiming at the drawbacks of the existing water-washable coating, the present invention utilizes a carbonizing agent and a polyhydroxy single-walled nanotube prepolymerization reaction, a porous carbon layer modifier and a glucose modifier chain extension, and a high carbonizing agent modification to solve the problem of polyurethane having no molten droplets and low heat release when heated, thereby improving the flame retardancy of the polyurethane; the water washability of the glucose modifier and the degradability of polycaprolactone diol and glucose are utilized to improve the degradability and water washability of the polyurethane.
[0012] The preparation method of the flame-retardant, water-washable, and drip-resistant water-based polyurethane coating is as follows:
[0013] (1) Raw material pretreatment: vacuum drying polytetrahydrofuran ether diol and polycaprolactone diol for 12 to 24 hours;
[0014] (2) Prepolymerization: 16-20 parts of polytetrahydrofuran ether diol, 8-10 parts of polycaprolactone diol, and 12-17 parts of isocyanate are added to a flask, 0.2-0.7 parts of dibutyltin dilaurate are dropped, a thermometer, a glass stopper, a stirring paddle, and a nitrogen tube are inserted into the mouth of the flask, the temperature is raised to 80-85° C., the rotation speed is 200-250 r / min, and the reaction is carried out for 1-2 hours. 4.7-5.2 parts of a carbonizing agent, 0.1-0.2 parts of a polyhydroxy single-walled polymer, and 0.05 parts of crotonic acid are added to the flask, and the reaction is carried out at 75-85° C. for 1.5-2.5 hours to obtain a polyurethane prepolymer;
[0015] (3) Chain extension: cool the polyurethane prepolymer to 45-55°C, add 1-2 parts of 2,2-dimethylol propionic acid, react for 1-2 hours, then add 1-1.5 parts of porous carbon layer modifier and 1.2-1.4 parts of glucose modifier, react at 65-70°C for 1-2 hours, then add 1-2 parts of triethylamine, react for 1-2 hours;
[0016] (4) Emulsification: cool to room temperature, add 140-170 parts of water, stir and react at a speed of 1000-1250 r / min for 1-2 hours, adjust the pH of the system to 7-8, and obtain a flame-retardant, water-washable, and drip-resistant water-based polyurethane coating.
[0017] The molecular weight of polytetramethylene glycol is 2000 g / mol, and the molecular weight of polycaprolactone glycol is 500 g / mol;
[0018] Isocyanate is any one of IPDI, HDI and MDI;
[0019] The preparation method of the carbon former is as follows: 12.3 g of p-hydroxybenzaldehyde is added into a beaker, and the mixture is stirred and dissolved with 180-280 mL of ethanol, and the mixture is poured into a 1000 mL three-necked flask, and the stirring speed is 250 r / min. The mixture is heated to 50-60° C., and 6.0-6.5 g of ethylenediamine diluted with 20 mL of ethanol is slowly dripped into the three-necked flask through a constant pressure dropping funnel, and the dripping time is 30 min. The reaction is continued for 1-2.5 h, and then 1.6-27.3 g of DOPO2 and 3.5-6.2 g of 3,4-epoxy-1-butene are added, and 0.74-1.85 g of initiator A is added. The mixture is reacted at 70-80° C. for 1-2 h, and the heating is stopped. The mixture is cooled to room temperature, filtered, washed with ethanol for 3 times, and vacuum dried at 60° C. for 18-24 h to obtain the carbon former.
[0020] The initiator A is any one of azobisisobutyronitrile and azobisisovaleronitrile.
[0021] The preparation method of the porous carbon layer modified material is as follows:
[0022] (1) Cut the vegetable tanned leather scraps into blocks with a length and width of 1 cm, place them in a vacuum tube furnace, heat them at 400° C. for 3 to 4 hours under a nitrogen atmosphere for pre-carbonization, mix the obtained carbonized product with KOH in a weight ratio of 1:3, then add 300% of water by weight to the mixture, and stir at 40 to 50° C. for 12 to 24 hours, then dry the product, and again carbonize and keep warm at 500 to 600° C. for 1 to 2 hours under nitrogen protection, and finally dry it to obtain a porous carbon layer;
[0023] (2) 0.5 g of porous carbon layer, 4.5-6.7 g of pyrrole, 2.26-3.14 g of DOPO, 0.7-1.4 g of 3,4-epoxy-1-butene, 100 mL of ethanol, 0.4-0.6 g of sodium p-toluenesulfonate, and 0.11-0.23 g of initiator B were stirred at 50-60° C. for 2-4 h, the product was dried, and 50 mL of DMF and 2.35-3.28 g of erythritol were added. The pH value is set to 7.5, and the reaction is stirred at 60-70°C for 1-2 hours. Then 2.74-3.15 g of phosphorus trichloride is added, and the reaction is carried out at 30-40°C for 1-2 hours. Then 5.98-6.21 g of myristic acid is added, and the reaction is carried out at 35-45°C for 1-2 hours. Then 6.24-8.62 g of neopentyl glycol is added, and the reaction is carried out at 50-60°C for 30-60 minutes. The product is dried to obtain a porous carbon layer modified product.
[0024] Initiator B is a mixture of benzoyl peroxide and ammonium persulfate in a weight ratio of 1.5:1.
[0025] The preparation method of glucose modification is as follows: add 1-1.3g of benzoyl chloride and 35mL of benzene to 4.1g of soluble glucose, stir and react at 30-40°C for 30-40min, rotary evaporate at 40-50°C, and dry to obtain glucose reaction product; then add 20mL of 70°C deionized water to the glucose modification, stir for 40-60min, add 0.04-0.06g of ammonium persulfate at 50-60°C to obtain soluble glucose A; at the same time, add 5.8g of propylene Mix 2.3 g hexadecyl dimethyl allyl ammonium chloride and 2 g N, N-methylene bis acrylamide, add them into 10 mL deionized water to dissolve, then slowly pour the solution into soluble glucose solution A, adjust the pH of the soluble glucose solution to 7.0 with 1 mol / L NaOH aqueous solution, stir at 50-70 ° C for 2-3 h, place in an electric blast drying oven at 90 ° C for reaction 2-3 h, and finally take out and dry for 24 h to obtain the glucose modification.
[0026] The advantages of the present invention are:
[0027] (1) A flame-retardant, washable, and molten-drip resistant water-based polyurethane coating was prepared, aiming to obtain a water-based flame-retardant polyurethane coating that can be washed with water and resistant to molten dripping after being immersed in water for a short time. The prepolymerization reaction of a carbonizing agent and polyhydroxy nanotubes was used, the compactness of the polyhydroxy nanotubes was enhanced by crotonic acid, the porous carbon layer modifier and the glucose modifier were used for chain extension, and the high carbonizing agent was used for modification, so that when the polyurethane was heated, no molten droplets were generated and the heat released was low, thereby improving the flame retardancy of the polyurethane; the water washability of the glucose modifier and the degradability of polycaprolactone diol and glucose were used to improve the degradability and water washability of the polyurethane;
[0028] (2) The present invention utilizes the aldehyde group of p-hydroxybenzaldehyde and the amino group of ethylenediamine to form a Schiff base through condensation of the aldehyde group and the imino group. This reaction occurs easily to generate an imine bond. Then, under the action of an initiator, the carbonizing agent intermediate, DOPO and 3,4-epoxy-1-butene undergo a free radical reaction, wherein the pH of DOPO reacts with the C=N or C=C double bond through an addition reaction. Ethylenediamine provides a nitrogen source and generates non-flammable gases such as nitrogen during combustion, causing the carbon layer to expand. p-hydroxybenzaldehyde and DOPO provide a carbon source and form a dense carbon layer covering the surface during combustion to isolate heat and oxygen. The phosphorus element in DOPO captures oxygen free radicals released by combustibles, reducing the possibility of combustion, thereby achieving a flame retardant effect.
[0029] (3) The present invention utilizes vegetable tanned leather scraps to be carbonized in a nitrogen atmosphere, isolating them from oxygen, and uses KOH to increase their fluffiness. The carbonization is continued to obtain a porous carbon layer. Pyrrole, DOPO and 3,4-epoxy-1-butene are dispersed in the porous carbon layer, and polymerization is carried out under the action of an initiator. The phase change material erythritol reacts with the NH bond of pyrrole, and the excess hydroxyl reacts with phosphorus trichloride. The excess phosphorus-chlorine bond reacts with myristic acid with a phase change. Then, neopentyl glycol with a high degree of branching and the excess phosphorus-chlorine bond are used to introduce hydroxyl groups into the system, so that a large amount of phase change material is introduced into the porous carbon layer. When the material is heated, it can absorb part of the heat and delay the possibility of combustion. At the same time, the porous carbon layer has a large amount of carbon, which reduces the possibility of combustion, and the hydroxyl group is used to react with the remaining isocyanate.
[0030] (4) The present invention utilizes part of the hydroxyl groups of soluble glucose to react with the acyl chloride of benzoyl chloride, utilizes the hydroxyl groups in the remaining glucose to react with the amino group or the imino group, and uses ammonium persulfate as an initiator to react acrylamide, hexadecyl dimethyl allyl ammonium chloride and N,N-methylene bis acrylamide in a free radical solution to form a soluble acrylic resin, and then accelerates the glucose reaction in an alkaline environment. The obtained soluble glucose has three functions: a) increasing the melting temperature of polyurethane, b) improving the water solubility of polyurethane, and c) increasing the swelling of polyurethane when heated and washed, so that it can be quickly peeled off from the epoxy resin PCB board to achieve moderate compatibility with the PCB board.
[0031] The part involved in the present invention is equivalent to g, and the soluble glucose is glucose. DETAILED DESCRIPTION
[0032] The present invention is further described below with reference to examples.
[0033] The chemical materials of unspecified manufacturers involved in the embodiments of the present invention can be replaced with similar products of Shanghai MacLean Biochemical Co., Ltd.
[0034] Embodiment 1
[0035] The preparation method of the flame retardant, washable, and drip-resistant water-based polyurethane coating is prepared according to the following method steps:
[0036] (1) Raw material pretreatment: vacuum drying polytetrahydrofuran ether diol (molecular weight 2000 g / mol) and polycaprolactone diol (molecular weight 500 g / mol) for 12 h;
[0037] (2) Prepolymerization: 16 parts of polytetrahydrofuran ether diol, 8 parts of polycaprolactone diol and 12 parts of IPDI were added into a flask, 0.2 parts of dibutyltin dilaurate were added dropwise, a thermometer, a glass stopper, a stirring paddle and a nitrogen tube were inserted into the mouth of the flask, the temperature was raised to 80°C, the speed was 200 r / min, and the reaction was carried out for 1 hour, 4.7 parts of a carbonizing agent, 0.1 parts of polyhydroxy single-walled carbon nanotubes and 0.05 parts of crotonic acid were added into the flask, and the reaction was carried out at 75°C for 1.5 hours to obtain a polyurethane prepolymer;
[0038] (3) Chain extension: The polyurethane prepolymer was cooled to 45°C, 1 part of 2,2-dimethylol propionic acid was added, and the reaction was continued for 1 hour. Then 1 part of porous carbon layer modifier and 1.2 parts of glucose modifier were added, and the reaction was continued at 65°C for 1 hour. Then 1 part of triethylamine was added, and the reaction was continued at 65°C for 1 hour.
[0039] (4) Emulsification: cool to room temperature, add 140 parts of water, stir and react at a speed of 1000 r / min for 1 hour, adjust the pH of the system to 7-8, and obtain a flame-retardant, water-washable, and drip-resistant water-based polyurethane coating.
[0040] The preparation method of the carbon former is as follows: 12.3 g of p-hydroxybenzaldehyde is added to a beaker, stirred and dissolved with 180 mL of ethanol, poured into a 1000 mL three-necked flask, stirred at a speed of 250 r / min, heated to 50°C, 6.0 g of ethylenediamine diluted with 20 mL of ethanol is slowly added dropwise to the three-necked flask through a constant pressure dropping funnel for 30 minutes, and the reaction is continued for 1 hour, and then DOPO21.6 g and 3,4-epoxy-1-butene 3.5 g are added, and 0.74 g of initiator azobisisobutyronitrile is added, and the reaction is carried out at 70°C for 1 hour, and heating is stopped, cooled to room temperature, filtered, washed with ethanol 3 times, and vacuum dried at 60°C for 18 hours to obtain a carbon former.
[0041] The preparation method of the porous carbon layer modified material is as follows:
[0042] (1) Cut the vegetable tanned leather scraps into blocks with a length and width of 1 cm, place them in a vacuum tube furnace, heat them at 400°C for 3 hours under a nitrogen atmosphere for pre-carbonization, mix the obtained carbonized product with KOH in a weight ratio of 1:3, then add 300% of its weight of water to the above mixture, and stir at 40°C for 12 hours, then dry the product, and again carbonize and keep warm at 500°C for 1 hour under nitrogen protection, and finally dry it to obtain a porous carbon layer;
[0043] (2) 0.5 g of porous carbon layer, 4.5 g of pyrrole, 2.26 g of DOPO, 0.7 g of 3,4-epoxy-1-butene, 100 mL of ethanol, 0.4 g of sodium p-toluenesulfonate, and 0.11 g of initiator B (a mixture of benzoyl peroxide and ammonium persulfate in a weight ratio of 1.5:1) were stirred at 50°C for 2 h, the product was dried, 50 mL of DMF and 2.35 g of erythritol were added, the pH was adjusted to 7.5, and the reaction was stirred at 60°C for 1 h. 2.74 g of phosphorus trichloride was added and the reaction was carried out at 30°C for 1 h. 5.98 g of myristic acid was added and the reaction was carried out at 35°C for 1 h. 6.24 g of neopentyl glycol was added and the reaction was carried out at 50°C for 30 min. The product was dried to obtain a porous carbon layer modified product.
[0044] The preparation method of the glucose modified material is as follows: add 1g of benzoyl chloride and 35mL of benzene to 4.1g of soluble glucose, stir and react at 30°C for 30min, rotary evaporate at 40°C, and dry to obtain a glucose reactant; then add 20mL of 70°C deionized water to the glucose reactant, stir for 40min, and add 0.04g of ammonium persulfate at 50°C to obtain soluble glucose A; at the same time, mix 5.8g of acrylamide, 2.3g of hexadecyldimethylallylammonium chloride and 2g of N,N-methylenebisacrylamide, add them to 10mL of deionized water to dissolve, then slowly pour the solution into the soluble glucose solution A, adjust the pH of the soluble glucose solution to 7.0 with a 1mol / L NaOH aqueous solution, stir and maintain at 50°C for 2h, place in an electric heated blast drying oven at 90°C for reaction for 2h, and finally take out and dry for 24h to obtain the glucose modified material.
[0045] Embodiment 2
[0046] The preparation method of the flame-retardant, water-washable, and drip-resistant water-based polyurethane coating is as follows:
[0047] (1) Raw material pretreatment: polytetrahydrofuran ether diol (molecular weight 2000 g / mol) and polycaprolactone diol (molecular weight 500 g / mol) were vacuum dried for 24 h;
[0048] (2) Prepolymerization: 20 parts of polytetrahydrofuran ether diol, 10 parts of polycaprolactone diol and 17 parts of HDI were added to a flask, 0.7 parts of dibutyltin dilaurate were added dropwise, a thermometer, a glass stopper, a stirring paddle and a nitrogen tube were inserted into the mouth of the flask, the temperature was raised to 85°C, the speed was 250 r / min, and the reaction was carried out for 2 hours, 5.2 parts of a carbonizing agent, 0.2 parts of polyhydroxy single-walled carbon nanotubes and 0.05 parts of crotonic acid were added to the flask, and the reaction was carried out at 85°C for 2.5 hours to obtain a polyurethane prepolymer;
[0049] (3) Chain extension: The polyurethane prepolymer was cooled to 55°C, 2 parts of 2,2-dimethylol propionic acid were added, and the reaction was continued for 2 h. Then 1.5 parts of porous carbon layer modifier and 1.4 parts of glucose modifier were added, and the reaction was continued at 70°C for 2 h. Then 2 parts of triethylamine were added, and the reaction was continued at 70°C for 2 h.
[0050] (4) Emulsification: cool to room temperature, add 170 parts of water, stir and react at a speed of 1250 r / min for 2 hours, adjust the pH of the system to 7-8, and obtain a flame-retardant, water-washable, and drip-resistant water-based polyurethane coating.
[0051] The preparation method of the carbon former is as follows: 12.3 g of p-hydroxybenzaldehyde is added to a beaker, stirred and dissolved with 280 mL of ethanol, poured into a 1000 mL three-necked flask, stirred at a speed of 250 r / min, heated to 60°C, 6.5 g of ethylenediamine diluted with 20 mL of ethanol is slowly added dropwise to the three-necked flask through a constant pressure dropping funnel, the addition time is 30 min, the reaction is continued for 2.5 h, DOPO27.3 g and 3,4-epoxy-1-butene 6.2 g are added, 1.85 g of azobisisovaleronitrile as initiator is added, the reaction is carried out at 80°C for 2 h, heating is stopped, cooled to room temperature, filtered, washed with ethanol 3 times, and vacuum dried at 60°C for 24 h to obtain a carbon former.
[0052] The preparation method of the porous carbon layer modified material is as follows:
[0053] (1) Cut vegetable tanned leather scraps into blocks with a length and width of 1 cm, place them in a vacuum tube furnace, heat them at 400°C for 4 hours under a nitrogen atmosphere for pre-carbonization, mix the obtained carbonized product with KOH in a weight ratio of 1:3, then add 300% of its weight of water to the mixture, and stir at 50°C for 24 hours, then dry the product, and again carbonize and keep warm at 600°C for 2 hours under nitrogen protection, and finally dry it to obtain a porous carbon layer;
[0054] (2) 0.5 g of porous carbon layer, 6.7 g of pyrrole, 3.14 g of DOPO, 1.4 g of 3,4-epoxy-1-butene, 100 mL of ethanol, 0.6 g of sodium p-toluenesulfonate, and 0.23 g of initiator B (a mixture of benzoyl peroxide and ammonium persulfate in a weight ratio of 1.5:1) were stirred at 60°C for 4 h, the product was dried, 50 mL of DMF and 3.28 g of erythritol were added, the pH was adjusted to 7.5, and the reaction was stirred at 70°C for 2 h. 3.15 g of phosphorus trichloride was added and the reaction was carried out at 40°C for 2 h. 6.21 g of myristic acid was added and the reaction was carried out at 45°C for 2 h. 8.62 g of neopentyl glycol was added and the reaction was carried out at 60°C for 60 min. The product was dried to obtain a porous carbon layer modified product.
[0055] The preparation method of the glucose modifier is as follows: 1.3 g of benzoyl chloride and 35 mL of benzene are added to 4.1 g of soluble glucose, the mixture is stirred at 40°C for 40 min, the mixture is rotary evaporated at 50°C, and the glucose reactant is dried; 20 mL of deionized water at 70°C is added to the glucose reactant, the mixture is stirred for 60 min, and 0.06 g of ammonium persulfate is added at 60°C to obtain soluble glucose A; at the same time, 5.8 g of acrylamide, 2.3 g of hexadecyldimethylallylammonium chloride and 2 g of N,N-methylenebisacrylamide are mixed, added to 10 mL of deionized water to dissolve, and then the solution is slowly poured into the soluble glucose solution A, the pH of the soluble glucose solution is adjusted to 7.0 with a 1 mol / L NaOH aqueous solution, the mixture is stirred at 70°C for 3 h, the mixture is placed in an electric blast drying oven at 90°C for reaction for 3 h, and finally the mixture is taken out and dried for 24 h to obtain the glucose modifier.
[0056] Embodiment 3
[0057] The preparation method of the flame-retardant, washable and drip-resistant water-based polyurethane coating is prepared by the following method:
[0058] (1) Raw material pretreatment: vacuum drying polytetrahydrofuran ether diol (molecular weight 2000 g / mol) and polycaprolactone diol (molecular weight 500 g / mol) for 18 h;
[0059] (2) Prepolymerization: 18 parts of polytetrahydrofuran ether diol, 9 parts of polycaprolactone diol and 14.5 parts of MDI were added to a flask, 0.45 parts of dibutyltin dilaurate were dropped into it, a thermometer, a glass stopper, a stirring paddle and a nitrogen tube were inserted into the mouth of the flask, the temperature was raised to 85°C, the speed was 225 r / min, and the reaction was carried out for 1.5 hours. 4.95 parts of a carbonizing agent, 0.15 parts of polyhydroxy single-walled carbon nanotubes and 0.05 parts of crotonic acid were added to the flask, and the reaction was carried out at 80°C for 2 hours to obtain a polyurethane prepolymer;
[0060] (3) Chain extension: The polyurethane prepolymer was cooled to 50°C, 1.5 parts of 2,2-dimethylol propionic acid was added, and the reaction was continued for 1.5 hours. Then 1.25 parts of porous carbon layer modifier and 1.3 parts of glucose modifier were added, and the reaction was continued at 65°C for 1.5 hours. Then 1.5 parts of triethylamine was added, and the reaction was continued at 65°C for 1.5 hours.
[0061] (4) Emulsification: cool to room temperature, add 155 parts of water, stir and react at a speed of 1100 r / min for 1.5 hours, adjust the pH of the system to 7-8, and obtain a flame-retardant, water-washable, and drip-resistant water-based polyurethane coating.
[0062] The preparation method of the carbon-forming agent is as follows: add 12.3g of p-hydroxybenzaldehyde into a beaker, stir and dissolve with 230mL of ethanol, pour into a 1000mL three-necked flask, stir at a speed of 250r / min, heat to 55°C, slowly drop 6.25g of ethylenediamine diluted with 20mL of ethanol into the three-necked flask through a constant pressure dropping funnel, the dropping time is 30min, continue to react for 1.75h, then add DOPO24.4g and 3,4-epoxy-1-butene 4.85g, add 1.3g of azobisisobutyronitrile, react at 75°C for 1.5h, stop heating, cool to room temperature, filter, wash with ethanol 3 times, and vacuum dry at 60°C for 21h to obtain a carbon-forming agent.
[0063] The preparation method of the porous carbon layer modified material is as follows:
[0064] (1) Cut vegetable tanned leather scraps into blocks with a length and width of 1 cm, place them in a vacuum tube furnace, heat them at 400°C for 3.5 hours under a nitrogen atmosphere for pre-carbonization, mix the obtained carbonized product with KOH in a weight ratio of 1:3, then add 300% of water by weight to the mixture, and stir at 45°C for 18 hours, then dry the product, and again carbonize and keep warm at 550°C for 1.5 hours under nitrogen protection, and finally dry it to obtain a porous carbon layer;
[0065] (2) 0.5 g of porous carbon layer, 5.6 g of pyrrole, 2.7 g of DOPO, 1.05 g of 3,4-epoxy-1-butene, 100 mL of ethanol, 0.5 g of sodium p-toluenesulfonate, and 0.17 g of initiator B (a mixture of benzoyl peroxide and ammonium persulfate in a weight ratio of 1.5:1) were stirred at 55°C for 3 h, the product was dried, 50 mL of DMF and 2.9 g of erythritol were added, the pH was adjusted to 7.5, and the reaction was stirred at 65°C for 1.5 h. 2.94 g of phosphorus trichloride was added and the reaction was carried out at 35°C for 1.5 h. 6.2 g of myristic acid was added and the reaction was carried out at 40°C for 1.5 h. 7.43 g of neopentyl glycol was added and the reaction was carried out at 55°C for 45 min. The product was dried to obtain a porous carbon layer modified product.
[0066] The preparation method of the glucose modified material is as follows: 1.15 g of benzoyl chloride and 35 mL of benzene are added to 4.1 g of soluble glucose, the mixture is stirred at 35° C. for 35 min, the mixture is rotary evaporated at 45° C., and the glucose reactant is dried; 20 mL of deionized water at 70° C. is added to the glucose reactant, the mixture is stirred for 45 min, and 0.05 g of ammonium persulfate is added at 55° C. to obtain soluble glucose A; at the same time, 5.8 g of acrylamide, 2.3 g of hexadecyldimethylallylammonium chloride and 2 g of N,N-methylenebisacrylamide are mixed, added to 10 mL of deionized water to dissolve, and then the solution is slowly poured into the soluble glucose solution A, the pH of the soluble glucose solution is adjusted to 7.0 with a 1 mol / L NaOH aqueous solution, the mixture is stirred at 60° C. for 2.5 h, the mixture is placed in an electric blast drying oven at 90° C. for reaction for 2.5 h, and finally the mixture is taken out and dried for 24 h to obtain the glucose modified material.
[0067] The prepared polyurethane coating was poured into a polytetrafluoroethylene mold with a thickness of 3 mm, and tests such as a droplet test and a cone calorimeter were performed.
[0068] Droplet test
[0069] (1) Sample preparation: The prepared polyurethane film was placed in a constant temperature and humidity chamber set at 23°C ± 0.5°C and 50% ± 5% humidity for 48 hours, after which it was taken out and cut into samples of 110 cm × 10 cm × 3 mm. Two sets of samples were prepared, with 5 samples in each set.
[0070] (2) Parameters: Clamp about 5mm from the top so that the sample is vertically downward, place a rosin board at the bottom of the sample, and pad about 0.3g of absorbent cotton on the board, evenly placed on the board. Adjust the gas flow rate to 105±5mL / min so that the flame height reaches 20±1mm. Set the combustion time to 10s.
[0071] (3) Flame recording: After setting the parameters, start the flame ignition. After the 10s ignition, press the afterflame time start button. When the sample combustion is finished and only sparks are left, press the afterflame combustion end button to enter the afterburning time. When the sample is completely extinguished, press the afterburning time end button and record the afterflame time and afterburning time.
[0072] (4) Molten droplet observation: During the combustion process, pay attention to whether the combustion produces molten droplets, and whether the molten droplets dripping onto the absorbent cotton below will cause secondary combustion, and record the observation results.
[0073] The test was carried out according to ASTM E1354-1990 (2004 standard) and the cone calorimeter 2000 of FTT Company of the United Kingdom was used for analysis and determination. The sample was 10cm×10cm, the thickness was 3mm, and the thermal radiation power was 12kW / m 2 , determine the maximum heat release rate pkHHR kW / m 2、THR total heat release MJ / m 2 .
[0074] Take 28 parts of the polyurethane coating of Examples 1 to 3, 0.3 parts of carboxymethyl fiber, 3.5 parts of polyvinyl pyrrolidone PVP-K30, 2 parts of polyvinyl alcohol, 5 parts of polyethylene glycol, and 1.5 parts of polyoxyethylene polypropylene ether, add them to 30 parts of distilled water in sequence, stir evenly, add 2.0 parts of polypropylene glycol (PPG-400), 0.5 parts of leveling agent, and 0.7 parts of silane coupling agent, stir evenly, filter and let stand to defoam, and then spray.
[0075] The composite coatings of Examples 1 to 3 were sprayed on the epoxy resin circuit board respectively, dried at 70° C. for 30 min, and then washed with a 50° C. warm water solution (temperature controlled at 50° C., KMnO4 50 g / L, potassium manganate 10 g / L, amplitude controlled at 20 mm / s, sodium hydroxide 1 mol / L, and the rest was water);
[0076] Water washing test method: Determination of the film removal time of the reference mixed liquid coating [1] Xie Dan, Jia Danfeng. About water-washable temporary protective coatings [J]. Aging and Application of Synthetic Materials, 2017, 46(5): 43-50.
[0077] The PCB hole position accuracy is measured by sampling and slicing under a metallographic microscope, and the hole wall roughness is measured by a secondary element device; the hole position accuracy, hole wall roughness, and hole diameter melt are sprayed with an application solution (coating thickness 0.04mm) on an aluminum foil (0.1mm), and then drilled on the lower PCB board.
[0078] The drill bit temperature is measured using a hot red temperature detector;
[0079] The pore size melt is observed by naked eyes, and the results are compared and divided into small, less and more data (if less than 30 holes have melt out of 100 holes, it is defined as small, 31 to 70 holes are less, and 71 to 100 holes are more);
[0080] Degradability test: Cut the matured polyurethane film into pieces with a length of 50 mm, a width of 50 mm and a thickness of 3 mm, and weigh them (m1). The treated polyurethane film samples are buried in moist soil rich in microorganisms and kept at a constant temperature of 25°C. After 30 days, the polyurethane film samples are taken out and washed with deionized water to remove surface impurities. The washed samples are placed in a blast drying oven at 40°C and dried to constant weight, and their weight is weighed and recorded (m2). The degradation rate is (m1-m2) divided by m1 and then multiplied by 100%.
[0081] Table 1 Film-forming properties of flame-retardant, water-washable and drip-resistant water-based polyurethane coatings
[0082]
[0083]
[0084] From Table 1, the flame retardancy (burning droplet phenomenon), pkHHR, and THR of the polyurethane film are significantly improved compared with the comparative example (Example 3 of 2023111285422); the present invention is superior to the comparative document in terms of water washability, hole position accuracy, hole wall roughness, drill bit temperature and aperture melt. The present invention has moderate adhesion, excellent degradation rate, less PCB board aperture melt, and is easy to clean. After the drill bit is heated, the film around the aluminum cover plate is almost not bonded, while in the comparative document, the film around the aluminum cover plate is bonded after the drill bit is heated, and there is a lot of PCB board aperture melt, which is difficult to clean.
[0085] Table 2 Flame retardant, washable, and drip resistant water-based polyurethane coating properties
[0086]
[0087]
[0088] As can be seen from Table 2, the carbonizing agent not only affects the flame retardancy of the polyurethane film (pkHHR, THR and molten droplet), but also affects the drilling accuracy and pore roughness (polyurethane sprayed on the aluminum cover plate, the drilling accuracy and pore roughness of the PCB and the pore melt) and the drill temperature. As can be seen from Table 2, the indicators without the addition of the carbonizing agent are not as good as those with the above substances. The addition of polyhydroxy carbon nanotubes and crotonic acid forms a dense carbon layer on the combustion surface of the polyurethane, which reduces the pkHHR and THR.
[0089] Table 3 Effect of porous carbon layer modification on the application properties of flame retardant, water-washable and drip-resistant water-based polyurethane coatings
[0090]
[0091]
[0092] As shown in Table 3, the porous carbon layer modifier, phosphorus trichloride, myristic acid and erythritol can improve the flame retardancy, hole position accuracy and hole wall roughness of the polyurethane resin, and neopentyl glycol affects the drill bit temperature and hole wall roughness of the drilling.
[0093] Table 4 Effects of glucose modifiers on flame retardant, water-washable, and drip-resistant water-based polyurethane coatings and their application properties
[0094]
[0095] As can be seen from Table 4, the hole position accuracy, hole wall roughness and water washability indexes decreased without the addition of the above substances, indicating that glucose modification, benzoyl chloride, N,N-methylenebisacrylamide and hexadecyldimethylallylammonium chloride played a core role.
[0096] The degradation rate without adding polycaprolactone diol was 12.4%, which also shows that polycaprolactone diol plays a degradation role.
Claims
1. A method for preparing a flame retardant, washable, and drip-resistant water-based polyurethane coating, characterized in that: (1) Raw material pretreatment: vacuum drying polytetrahydrofuran ether diol and polycaprolactone diol for 12 to 24 hours; (2) Prepolymerization: Add 16-20 parts of polytetrahydrofuran ether diol, 8-10 parts of polycaprolactone diol, and 12-17 parts of isocyanate into a flask, drop 0.2-0.7 parts of dibutyltin dilaurate, insert a thermometer, a glass stopper, a stirring paddle, and a nitrogen tube into the mouth of the flask, heat to 80-85°C, rotate at 200-250 r / min, and react for 1-2 hours. Add 4.7-5.2 parts of a carbonizing agent, 0.1-0.2 parts of polyhydroxy single-walled carbon nanotubes, and 0.05 parts of crotonic acid into the flask, and react at 75-85°C for 1.5-2.5 hours to obtain a polyurethane prepolymer. (3) Chain extension: Cool the polyurethane prepolymer to 45-55°C, add 1-2 parts of 2,2-dimethylolpropionic acid, react for 1-2 hours, then add 1-1.5 parts of porous carbon layer modifier and 1.2-1.4 parts of glucose modifier, react at 65-70°C for 1-2 hours, then add 1-2 parts of triethylamine, react for 1-2 hours; (4) Emulsification: cool to room temperature, add 140-170 parts of water, stir and react at a speed of 1000-1250 r / min for 1-2 hours, adjust the pH of the system to 7-8, and obtain a flame-retardant, washable, and drip-resistant water-based polyurethane coating.
2. The method for preparing the flame-retardant, washable, and drip-resistant water-based polyurethane coating according to claim 1, characterized in that: The molecular weight of the polytetramethylene ether diol is 2000 g / mol, and the molecular weight of the polycaprolactone diol is 500 g / mol.
3. The method for preparing the flame-retardant, washable, and drip-resistant water-based polyurethane coating according to claim 1, characterized in that: The isocyanate is any one of IPDI, HDI and MDI.
4. The method for preparing the flame-retardant, washable, and drip-resistant water-based polyurethane coating according to claim 1, characterized in that: The carbon-forming agent preparation method comprises the following steps: adding 12.3 g of p-hydroxybenzaldehyde into a beaker, stirring and dissolving it with 180-280 mL of ethanol, pouring the mixture into a 1000 mL three-necked flask, stirring at a speed of 250 r / min, heating the mixture to 50-60° C., slowly dropping 6.0-6.5 g of ethylenediamine diluted with 20 mL of ethanol into the three-necked flask through a constant pressure dropping funnel, dropping for 30 minutes, continuing the reaction for 1-2.5 hours, then adding 21.6-27.3 g of DOPO and 3.5-6.2 g of 3,4-epoxy-1-butene, adding 0.74-1.85 g of initiator A, reacting at 70-80° C. for 1-2 hours, stopping heating, cooling the mixture to room temperature, suction filtering, washing with ethanol for 3 times, and vacuum drying at 60° C. for 18-24 hours to obtain the carbon-forming agent.
5. The method for preparing the flame-retardant, washable, and drip-resistant water-based polyurethane coating according to claim 4, characterized in that: The initiator A is any one of azobisisobutyronitrile and azobisisovaleronitrile.
6. The method for preparing the flame-retardant, washable, and drip-resistant water-based polyurethane coating according to claim 1, characterized in that: The preparation method of the porous carbon layer modified material is as follows: (1) Cut the vegetable tanned leather scraps into blocks with a length and width of 1 cm, place them in a vacuum tube furnace, heat them at 400°C for 3-4 hours under a nitrogen atmosphere for pre-carbonization, mix the obtained carbonized product with KOH in a weight ratio of 1:3, then add 300% water by weight to the above mixture, and stir at 40-50°C for 12-24 hours, then dry the product, and again carbonize and keep warm at 500-600°C for 1-2 hours under nitrogen protection, and finally dry it to obtain a porous carbon layer; (2) 0.5 g of porous carbon layer, 4.5-6.7 g of pyrrole, 2.26-3.14 g of DOPO, 0.7-1.4 g of 3,4-epoxy-1-butene, 100 mL of ethanol, 0.4-0.6 g of sodium p-toluenesulfonate, and 0.11-023 g of initiator B were stirred at 50-60 °C for 2-4 h. The product was dried, and then 50 mL of DMF and 2.35-3.28 g of erythritol were added to adjust the The pH value is 7.5, and the reaction is stirred at 60-70°C for 1-2 hours. Then, 2.74-3.15 g of phosphorus trichloride is added, and the reaction is carried out at 30-40°C for 1-2 hours. Then, 5.98-6.21 g of myristic acid is added, and the reaction is carried out at 35-45°C for 1-2 hours. Then, 6.24-8.62 g of neopentyl glycol is added, and the reaction is carried out at 50-60°C for 30-60 minutes. The obtained product is dried to obtain a porous carbon layer modified product.
7. The method for preparing the flame-retardant, washable, and drip-resistant water-based polyurethane coating according to claim 6, characterized in that: The initiator B is a mixture of benzoyl peroxide and ammonium persulfate in a weight ratio of 1.5:
1.
8. The method for preparing the flame-retardant, washable, and drip-resistant water-based polyurethane coating according to claim 1, characterized in that: The preparation method of the glucose modified substance is as follows: 1-1.3 g of benzoyl chloride and 35 mL of benzene are added to 4.1 g of soluble glucose, the mixture is stirred at 30-40° C. for 30-40 min, the mixture is rotary evaporated at 40-50° C., and the glucose reactant is dried; 20 mL of 70° C. deionized water is added to the glucose reactant, the mixture is stirred for 40-60 min, and 0.04-0.06 g of ammonium persulfate is added at 50-60° C. to obtain soluble glucose A; 5.8 g of acrylamide, 2.3 g of hexadecyldimethylallylammonium chloride and 2 g of N,N-methylenebisacrylamide are mixed, added to 10 mL of deionized water to dissolve, and then the solution is slowly poured into the soluble glucose solution A, the pH of the solution is adjusted to 7.0 with 1 mol / L NaOH, the solution is stirred at 50-70° C. for 2-3 h, the mixture is placed in an electric blast drying oven at 90° C. for 2-3 h, and finally the mixture is taken out and dried for 24 h to obtain the glucose modified substance.
Citation Information
Patent Citations
A manufacturing method to improve the accuracy of back drilling on PCB boards
CN103533761B
Gluing aluminum-based cover plate for PCB drilling and preparing method thereof
CN110281308A
Washable temporary decorative coating for soft PVC (polyvinyl chloride) as well as preparation method and application of washable temporary decorative coating
CN114921135A
Tertiary amine type flame-retarding curing agent for epoxy resin and its preparation method
CN108148095A
P-aminobenzoic acid condensed p-hydroxy Schiff base / DOPO flame retardant, preparation method thereof and modified epoxy resin
CN113429627A
Cited By
Preparation method of flame-retardant, high-refraction and melt-drop-resistant polyurethane coating
CN119842310A
Preparation Method of Flame Retardant, High Refractive Index and Melting Drop-Resistant Polyurethane Coating
CN119842310B